Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.